2019
DOI: 10.1101/816124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A widespread family of heat-resistant obscure (Hero) proteins protect against protein instability and aggregation

Abstract: Proteins are typically denatured and aggregated by heat. Exceptions to this principle include highly disordered and heat-resistant proteins found in extremophiles, which help these organisms tolerate extreme conditions such as drying, freezing, and high salinity.In contrast, the functions of heat-soluble proteins in non-extremophilic organisms including humans remain largely unexplored. Here we report that heat-resistant obscure (Hero) proteins, which remain soluble after boiling at 95ºC, are widespread in Dro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(45 citation statements)
references
References 58 publications
7
38
0
Order By: Relevance
“…A final intriguing hypothesis is that BUBL-1 is involved in protein aggregation. C9orf16 was found in a search for highly heat-resistant proteins that remain soluble upon boiling (Tsuboyama et al, 2020). The identified proteins, termed 'Hero' for heat-resistant obscure proteins, were shown to protect different subsets of proteins from aggregation or denaturation under stress conditions (Tsuboyama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A final intriguing hypothesis is that BUBL-1 is involved in protein aggregation. C9orf16 was found in a search for highly heat-resistant proteins that remain soluble upon boiling (Tsuboyama et al, 2020). The identified proteins, termed 'Hero' for heat-resistant obscure proteins, were shown to protect different subsets of proteins from aggregation or denaturation under stress conditions (Tsuboyama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…C9orf16 was found in a search for highly heat-resistant proteins that remain soluble upon boiling (Tsuboyama et al, 2020). The identified proteins, termed 'Hero' for heat-resistant obscure proteins, were shown to protect different subsets of proteins from aggregation or denaturation under stress conditions (Tsuboyama et al, 2020). Indeed, C9orf16 is differentially expressed in diseases characterized by protein aggregation, including amyotrophic lateral sclerosis (ALS) (Nijssen et al, 2018), Alzheimer's (Kong et al, 2009), and Parkinson's disease (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Kotaro Tsuboyama (The University of Tokyo) presented his recent finding on the new Hero protein family (Tsuboyama et al 2019). From the classical point of view, folding is a fundamental feature of the "protein."…”
Section: Main Textmentioning
confidence: 99%
“…These newly discovered peptides lack known conserved domains and thus have long been overlooked by functional predictions based on primary sequence analyses. Studies have also shown that a group of novel proteins, entirely consisting of intrinsically disordered regions, possesses outstanding molecular properties to inhibit the formation of disease‐related molecular aggregates or protect DNA from irradiation (Hashimoto et al, 2016; Tsuboyama et al, 2020). Interestingly, at least two of these "superdisordered" proteins maintain their molecular activity even after the random shuffling of their primary amino acid sequences (Tsuboyama et al, 2020), suggesting that the function of these superdisordered proteins is dependent on the composition of the amino acids rather than their primary sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that a group of novel proteins, entirely consisting of intrinsically disordered regions, possesses outstanding molecular properties to inhibit the formation of disease‐related molecular aggregates or protect DNA from irradiation (Hashimoto et al, 2016; Tsuboyama et al, 2020). Interestingly, at least two of these "superdisordered" proteins maintain their molecular activity even after the random shuffling of their primary amino acid sequences (Tsuboyama et al, 2020), suggesting that the function of these superdisordered proteins is dependent on the composition of the amino acids rather than their primary sequences. The functional independence of the amino acid sequences makes it difficult to predict the function of these proteins by conventional bioinformatics analyses.…”
Section: Introductionmentioning
confidence: 99%